Implementasi Triple Bottom Line Untuk Pengembangan Ekowisata Sungai Berkelanjutan: Studi Kasus Lewu Rawan Bahalap Kalimantan Tengah - Damayanti, Frillia; Sari, Cyntia Lupita; Larissa, Kania; Frins, Viola Valencia (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2026)
This study develops a strategic framework based on the Triple Bottom Line (TBL) to analyze the sustainability optimization of river-based ecotourism within peatland wetland ecosystems, with a focus on Lewu Rawan Bahalap in Palangka Raya City, Central Kalimantan. Despite challenges such as limited capital and the need for rehabilitation of former sand mining areas, this destination has demonstrated positive growth in tourist visits. The study employs a qualitative-descriptive approach through a literature review, utilizing secondary data from academic sources and policy documents. The analysis focuses on the three TBL dimensions, People, Planet, and Profit. The findings indicate that while the destination possesses strengths in cultural authenticity and ecosystem uniqueness, it requires improvements in structured ecological restoration programs, diversified financing mechanisms, sustainable environmental monitoring systems, and strategic partnerships. This study proposes a sustainable development model consisting of five key components: collaborative governance, monitoring systems, capacity building, innovative financing (including Payment for Ecosystem Services), and adaptive resilience. The contribution of this research lies in the formulation of a strategic framework applicable to family-based ecotourism enterprises within post-extractive peatland ecosystems.